1999
DOI: 10.1088/0031-9155/44/6/307
|View full text |Cite
|
Sign up to set email alerts
|

A CCD-based system for the detection of DNA in electrophoresis gels by UV absorption

Abstract: A method and apparatus for the detection and quantification of large fragments of unlabelled nucleic acids in agarose gels is presented. The technique is based on ultraviolet (UV) absorption by nucleotides. A deuterium source illuminates individual sample lanes of an electrophoresis gel via an array of optical fibres. As DNA bands pass through the illuminated region of the gel the amount of UV light transmitted is reduced because of absorption by the DNA. During electrophoresis the regions of DNA are detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
3
1
Order By: Relevance
“…The pellet obtained by centrifugation was also examined on agarose gel under UV light, which yielded no DNA bands. It has been reported that non‐covalent NH 2 ‐MWCNT‐DNA complex with a tendency to aggregate could not move through the agarose gel, and it is not visible on agarose gel . Similarly, we could not observe the presence of bound DNA.…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…The pellet obtained by centrifugation was also examined on agarose gel under UV light, which yielded no DNA bands. It has been reported that non‐covalent NH 2 ‐MWCNT‐DNA complex with a tendency to aggregate could not move through the agarose gel, and it is not visible on agarose gel . Similarly, we could not observe the presence of bound DNA.…”
Section: Resultscontrasting
confidence: 54%
“…This could be attributed to the absence of unbound mpDNA, or that the samples were below detection limit. EtBr has a detection limit of 2–10 ng, and we introduced 4.9 µg mpDNA into the reaction. Thus, regarding the binding yield of mpDNA, the presence of DNA at ng levels could be negligible compared to µg level.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover a number of digital imaging systems for nonionizing imaging applications in life science have being developed in the last two decades, mainly based on the use of CCDs [11] [12] [13] [14] and single avalanche diodes [15]. Even so these systems exhibit serious shortcomings in imaging performance, such as a low frame rate due to the inherent sequential read-out, require operation at low temperature to achieve a reasonable noise level or suffer from poor geometrical efficiency due to the optics involved.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless it presents key drawbacks such as a limited and non linear dynamic range. Coupled Device (CCD) both as prototypes [2][3] and commercially available systems [4] [5]. Even so these system present several limitations in imaging performance, such as low frame rate due to the sequential read out, and require operations at low temperature to achieve reasonable noise level.…”
Section: Introductionmentioning
confidence: 99%